L-Fuzzy Filters of a Poset - Berhanu Assaye Alaba; Mihret Alamneh; Derso Abeje (LPPM Institut Teknologi Sepuluh Nopember, 2019)
Many generalizations of ideals and filters of a lattice to an arbitrary poset have been studied by different scholars. The authors of this paper introduced several generalizations of L-fuzzy ideal of a lattice to an arbitrary poset in [1]. In this paper, we introduce several L-fuzzy filters of a poset which generalize the L-fuzzy filter of a lattice and give several characterizations of them.